METODE PEMBELAJARAN âPICTURE AND PICTUREâ DALAM MENULIS TEKS CERITA FIKSI NOVEL PADA BUKU TEKS BAHASA INDONESIA EKSPRESI DIRI DAN AKADEMIK SMA/ MA/ SMK/ MAK KELAS X11 SEMESTER 2 KURIKULUM 2013 (BAHASTRA, 2017)
This study expects a teacher has learning methods to better support classroom learning, thus resulting in a productive and active learning. Indonesian textbooks and academic self-expression SMA / MA / SMK / MAK class XII 2nd semester curriculum in 2013, the Ministry of education and culture through learning to write fiction in the novel. This study uses a method that is Pictur Picture and Picture and Picture Learning model is a learning method that uses images and paired or sorted into a logical sequence. Learning is characterized Active, Innovative, Creative, and Fun. Learning Model relies images as a medium of learning. These images become a major factor in the learning process. In pulling teaching of writing fiction in the novel, the author tried to examine the learning method and Pictur Picture.Â Â